IDENTIFYING WHAT SERVICES NEED TO BE IMPROVED BY MEASURING THE LIBRARY’S PERFORMANCE - Johari, Roslah; A.N., Zainab (Malaysian Journal of Library and Information Science, 2017)
This is an exploratory attempt to use a modified version of SERVPERF to assess user’s satisfaction with the services provided by an ISO9000:2000 certified library at a private university in Malaysia where measuring performance would be an integral part to continuously improve quality of services. The services being measured are grouped as frontline, core and peripheral where staff and facilities interact with users directly and where user’s opinions and expectations could be extracted. The clients are undergraduates and postgraduates who use these services and facilities. The results identify services deem important to users of the library as well as the problem areas which need improvements. A total of 274 students comprising 250 undergraduates and 24 postgraduates form the sample. The respondents’ ratings range on average between 3.13 and 4.36 on a 5-point scale, implying that the library is performing at an above average level. From 59 service attributes, 2 are perceived as excellent, 20 attributes are considered good, 31 are average and 4 services are rated as poor. A total of 16 services are rated below 50%, which form the priority list of services given priority in the library’s proposed action plan. The good and excellent services would continue to be monitored to maintain their performance